(untitled) (Anclajes, 2023)
In Memorias de un hombre de izquierda (1976), the Mexican intellectual Víctor Manuel Villaseñor (1903-1981) was eager to demonstrate his political, professional, and ideological consistency throughout his life. Two cornerstones of this discourse are the accounts of his two journeys to the Soviet Union, which description connects with the literary sub-genre of the travelogue to the USSR. Villaseñor uses these episodes to present himself as an “expert” on the Soviet world whose opinion is supported by his direct knowledge of reality. Through the analysis of both episodes, therefore, we apprehend the image of the Soviet Union of the 1930s and 1940s still held by the old Mexican pro-Soviet left in the 1970s and demonstrate how these travel narratives were used to justify political positions, knowledge, reasoning and historical interpretations even decades after the original moment in which the trips were made.